V.A. Gorbatov theory of characterization: Principles and examples - Tadeusz Krupa (Foundations of Management, 2013)
Characterization theory was developed in the 1970s by a member of the Russian Academy of Sciences, a prominent cybernetics V.A. Gorbatov, and became the nucleus of an international school. Many of today's academy graduates make a new generation of scholars, more than 150 doctors and assistant professors, developing a new descriptive theory of cybernetic complex systems, based on the canon of the so-called characterization principle, binding the sets of y¥a functioning models and x¥bstructure models using the paradigm of monotone mappings of the considered system. This article presents an overview of the following problems: (1) the issues of functional-structural connection systems from the point of view of their design correctness; (2) the basic postulates of the characterization principle; (3) the nature of interaction between system objects; (4 and 5) mechanisms and functions for initiation of the operation; (6) the mechanisms of control and reaction functions; (7 and 8) the analytical form of initiation function and a network initialization function and (9) the axiom of extensionality (J), feasibility (R) and compatibility (Z).
Keywords: 650; functional model; structure model; atomic predicate; characterization principle; operations and functions of initiation; control and response functions; axioms of clarity; feasibility and compatibility